The Role of Parents in Instilling the Habits of Obligatory Prayer, Reading the Qur'an, and Fasting During Ramadan in 10-Year-Old Children in the Family Environment - Albarqi Surosentono; Astuti Darmiyanti; Vismaia Nur Fitriani (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the role of parents in instilling the habits of obligatory prayer, reading the Qur'an, and fasting during Ramadan in 10-year-old children within the family environment. The study used a qualitative approach with descriptive methods. Data collection techniques were carried out through interviews, observation, and documentation of parents of 10-year-old children. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that parents have a very important role in forming children's worship habits through role models, habituation, mentoring, supervision, and motivation. Modeling is done by providing direct examples in carrying out worship, while habituation is done through routine worship implementation in daily life. Assistance is provided when children learn to read the Qur'an and perform worship, while supervision and motivation are carried out to maintain children's consistency in carrying out worship. Worship habits instilled include obligatory prayer, reading the Qur'an, and fasting during Ramadan. The research findings indicate that active parental involvement and a religious family environment are important factors in shaping children's religious character from an early age. Thus, the family has a strategic role in instilling religious values ​​and forming sustainable worship habits in children.